The Transformation of The Swing Procession: From Hereditary Tradition to The Modern Era - Ramadhan, Iwan; Mualimin, Mualimin (Universitas Tanjungpura, 2024)
The tradition of riding ayun in ethnic Malays in West Kalimantan is one form of cultural preservation that has undergone a significant transformation in the face of the modern era. This study aims to describe changes in the meaning, implementation, and interpretation of the swing riding tradition in the context of the modern era. The research method used is a qualitative method with an analytical descriptive study approach. Data was collected through observation and interviews with local communities who still preserve the tradition of riding Ayun. The results showed that the tradition of swinging rose experienced changes in meaning, implementation, and interpretation. The influence of technology and globalization plays an important role in this change. Technology enables the use of social media and event planning apps to make it easier for families planning traditional events to ride the swing. In addition, technology also allows the use of modern equipment in the implementation of traditions, such as the use of audio-visual equipment to display information about the tradition of swinging or documentation of the birth of a baby. On the globalization side, the tradition of swinging can become better known in different parts of the world through social media platforms and websites. This can help in expanding the appreciation of this tradition on a global level. This research suggests that cultural transformation can occur in hereditary traditions such as swing rides. Therefore, cultural preservation needs to be done in the right way so that the tradition remains relevant and can be passed on to the next generation. In addition, the study also shows that technology and globalization can play an important role in cultural preservation. Therefore, there needs to be an effort to leverage technology and global connectivity to promote and preserve local culture.